Singapore-Malaysia virtual community in 2020 : fast track to an economic union? - Yang Razali Kassim (2013)
The growing connectivity between Singapore and Malaysia accelerated this month with their two prime ministers announcing the launch of a high speed train link by 2020. will this exciting bilateral project be a fast track to an economic between the two countries.